Mania following ketamine abuse - Lu Y; Lin C; Lane H (Neuropsychiatric Disease and Treatment)
Yuan-Yuan Lu,1 Chieh-Hsin Lin,2,3 Hsien-Yuan Lane1,2,4 1Department of Psychiatry, China Medical University Hospital, 2Graduate Institute of Clinical Medical Science, China Medical University, Taichung, 3Department of Psychiatry, Kaohsiung Chang Gung Memorial Hospital, Chang Gung University College of Medicine, Kaohsiung, 4Center for Drug Abuse and Addiction, China Medical University Hospital, Taichung, Taiwan Abstract: Ketamine, a noncompetitive antagonist of the N-methyl-d-aspartate (NMDA) receptor, has multiple clinical uses. On the other hand, ketamine abuse or recreational use has been gaining increasing attention. Induction of mania and psychotic symptoms has been reported in a patient receiving IV ketamine therapy for reflex sympathetic dystrophy. We here report a 26 year-old man who abused ketamine by inhalation for 12 months and developed manic-like symptoms after ketamine use. This case suggests a possible relationship between manic symptoms and ketamine abuse. To the best of our knowledge, this may be the first report regarding mania after recreational use of ketamine. Keywords: ketamine, mania, antidepressant, bipolar